Comparative incidence and burden of respiratory viruses associated with hospitalization in adults in New York City. Issue 5 (26th January 2021) - Sieling, William D.; Goldman, Connor R.; Oberhardt, Matthew; Phillips, Matthew; Finelli, Lyn; Saiman, Lisa
Abstract: Background: Although the burden of influenza is well characterized, the burden of community‐onset non‐influenza respiratory viruses has not been systematically assessed. Understanding the severity and seasonality of non‐influenza viruses, including human coronaviruses, will provide a better understanding of the overall disease burden from respiratory viruses that could better inform resource utilization for hospitals and highlight the value of preventative strategies, including vaccines. Methods: From October 2017 to September 2019, a retrospective study was performed in a pre‐defined catchment area to estimate the population‐based incidence of community‐onset respiratory viruses associated with hospitalization. Included patients were ≥18 years old, resided in New York City, were hospitalized for ≥24 hours, and had a respiratory virus detected within 3 calendar‐days of admission. Disease burden was measured by hospital length of stay (LOS), intensive care unit (ICU) admissions, and in‐hospital mortality and compared among those with laboratory‐confirmed influenza versus those with laboratory‐confirmed non‐influenza viruses (human coronaviruses, parainfluenza viruses, respiratory syncytial virus, human metapneumovirus, and adenovirus). Results: During the study period, 4232 eligible patients were identified of whom 50.9% were ≥65 years of age. For each virus, the population‐based incidence was highest for those ≥80 years of age. When compared to those with influenza viruses detected, those with non‐influenza respiratory viruses detected (combined) had higher population‐based incidence, significantly more ICU admissions, and higher in‐house mortality. Conclusions: The burden of non‐influenza respiratory viruses for hospitalized adults is substantial. Prevention and treatment strategies are needed for non‐influenza respiratory viruses, particularly for older adults.